(3GdJfejI hGdScGfs - (3GMeO SGeQ(B, (3GdOYHhSjs ((3YeGf(B;(3GdQjGV(B:s (3ecJHI GdeLJeY GdYQHj ddfTQ hGdJhRjY(B;(3OGQ CLfGOjf ddfTQ hGdJhRjY,s, 2007)
(3jVe GdehGQO GdHTQjI CZdi eG Jedcg GdCeI, GdGJLGgGJ GdRefjI aj eLGd GdScGf hGdHjFI hGdJfejI, BQGA GdMcheGJ hSjGSGJgG GdeJYdbI HGdScGf hGdHjFI hGdJfejI, MLe GdScGf hGdfeh GdScGfj hGdHjFI hGdUMI, GdgLQI hGdJZjQ GdScGfj hGdHjFI GdQjajI, eYOdGJ GdhajGJ hGdNUhHI hGdHjFI hGdUMI, GdJfejI hGdHjFI hGdScGf aj GdefGWb GdMVQjI, GSJfJGLGJ, fXQjGJ hCWQ dfePLI CKQ Gdfeh GdScGfj Ydi GdHjFI GdeGOjI, GdTQGcI hJOab GdehGQO aj eLGd GdScGf hGdUMI GdGfLGHjI hGdJfejI, GdJhUjGJ GdehLgI Gdi GdMcheGJ, JOab GdehGQO, ebJQMGJs
(3HjHdjhZQGajG(B: (3U(B.173s
Keywords: (3GdJfejI GdELJeGYjIs; (3GdScGfs; (3Gdbhi GdYGedIs